Functional expression in primate cells of cloned DNA coding for the hemagglutinin surface glycoprotein of influenza virus. - Sveda, M M (1981)
We have used simian virus 40 (SV40) DNA as a vector for expression of functional activity of a cloned influenza viral DNA segment in primate cells. Cloned full-length DNA sequences coding for the hemagglutinin of influenza A virus (Udorn/72/[H3N2]) were inserted into the late region of a viable deletion mutant of SV40, and the hybrid DNA was propagated in the presence of an early SV40 mutant (tsA28) helper. Infection of primate cells with the hybrid virus produced a polypeptide similar in molecular size to the hemagglutinin of influenza virus, as shown by immunoprecipitation and gel electrophoresis. The polypeptide was glycosylated, as shown by incorporation of radioactive sugars. The putative hemagglutinin exhibited functional activity, as shown by agglutination of erythrocytes. In addition, an indirect immunofluorescence assay showed that the hemagglutinin polypeptide of the hybrid virus could be detected on the surface of infected cells.